Association between number of hyperbaric oxygen therapy sessions and neurocognitive outcomes of acute carbon monoxide poisoning - Lee, Je Seop; Cha, Yong Sung; Lim, Jihye (Frontiers in Medicine, 2023)
Background: Hyperbaric oxygen therapy (HBO2) is recommended for symptomatic patients within 24 h of carbon monoxide (CO) poisoning. Currently, there is no consensus on the number of HBO2 sessions within 24 h after arrival at the hospital. Therefore, we evaluated differences in the therapeutic effects according to the number of HBO2 sessions in acute CO poisoning. Methods: This cohort study included data collected from our CO poisoning registry and prospective cohorts between January 2006 and August 2021 in a single academic medical center in South Korea. Based on the number of HBO2 sessions performed within 24 h, we classified patients into one- and multiple- (two or three) session groups. We also compared mild (non-invasive mechanical ventilation) and severe (invasive mechanical ventilation) groups. CO-related neurocognitive outcomes were measured using the Global Deterioration Scale (GDS; stages: 1‒7) combined with neurological impairment at 1 month after poisoning. We classified GDS stages as favorable (1‒3 stages) and poor (4‒7 stages) neurocognitive outcomes. Patients belonging to a favorable group based on GDS assessment, but with observable neurological impairment, were assigned to the poor outcome group. Propensity score matching (PSM) was performed to adjust for age, sex, and related variables to identify statistical differences between groups. Results: We analyzed the data of 537 patients between ages 16 and 70 years treated with HBO2. After PSM, there was no significant difference in neurocognitive outcomes at 1 month among the two groups of patients (P=0.869). Furthermore, there were no significant differences in neurocognitive outcomes between invasive mechanical ventilation and non-invasive mechanical ventilation patients in the three groups (P=0.389 and P=0.295). Conclusion: There were no significant differences in the reduction of poor neurocognitive outcomes according to the number of HBO2 sessions implemented within 24 h of CO exposure.